(untitled) (Proceedings of Southern Federal University. Philology, 2014)
(Buslenko N. I. Journalism: sociological, legal and political changes. Selected works. T. II. Rostov n/D: Donskoy writer, 2013. 660 p.) Smejuha V. V. Keywords: Buslenko N. I. , journalism, institute of society, media, social structure. The author of this article analyzes in detail the book "Journalism: sociological, legal, political change" by Buslenko N. I. The author agrees with Buslenko that journalism, which is one of the institutions of society, not only demonstrates the evolutionary nature of the development, but also actively contributes to the implementation of innovative practices in various spheres of society. As the author says: the book is the result of observation process of the media establishment during many years, which allowed the author to make significant findings and conclusions in the fields of media functioning, its role in society and impact on the political, economic, social structure. The book is logically structured and will be essential in both practical and scientific communities, as well as in the educational process.